Sustentabilidade socioambiental em PMEs: pesquisa-ação em uma jornada de preparação para certificação como Empresa B - Silva, Fernando Oliani Vieira da (2023)
Small and medium-sized enterprises (SMEs) face several challenges to become sustainable in the socio-environmental dimension, as they have limited capacities and resources, and lack awareness, knowledge, and experience in sustainability. This study addresses the journey for preparing a small company, that was not born sustainable, to be certified as a B Corporation. B Corporations are private organizations that aim to generate positive socio-environmental impacts through their business activities. The purpose of this dissertation was to support this journey, using state-of-the-art knowledge on hybrid organizations and B Corporations, and extracting valuable lessons from this process for other companies. Therefore, it lies in the field of business transformation for sustainability. To meet the proposed goal, we chose the action research approach, and the following research question guided the field study: how to implement measures that help improve socio-environmental indicators in a small business? The study presented the following conclusions: i) the preparation journey for B Corporation certification enabled improving the company's socio-environmental indicators by using B Impact Assessment (BIA) as a tool to guide the necessary changes, assessing the business model to include socio-environmental impact, and providing education on sustainability for leaders; ii) the formalization of corporate governance and mechanisms that align socioenvironmental objectives with the company´s strategy are relevant to make it central to the business; iii) identifying opportunities resulting from the implementation of sustainable practices can be a leverage for sustainability. The study provided the following main contributions to theory: it broadened the understanding of the journey toward sustainable practices in a small company with a traditional profile; it highlighted the critical role that corporate governance can play, elucidating the reasons underlying its indispensability in establishing sustainability as a central agenda within the company. The main contributions to practice were: it enabled structuring a framework with suggestions for SMEs on how to overcome some of the barriers to sustainability; it emphasized the significance of considering sustainability as a strategic imperative, aligned with actions, objectives, and corporate governance for the journey.